Die Kontextuelle Theorie und ihre Relevanz für die Seelsorge an Menschen mit einer bleibenden Behinderung - KISS, Jenő (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Contextual Approach and Its Significance Concerning People with Permanent Disabilities. The purpose of this study is to present the contextual approach within spiritual care, as well as to show how important it is concerning a person’s life and relation-ships, with a special outlook towards those with permanent disabilities. To this end, it sketches the history of the formation of contextual therapy and spiritual care and describes its interpretation of human reality (I). Further, it presents the most elementary features of created human existence (theological anthropology). Based on the Creation Story and Karl Barth’s doctrine concerning creation, it draws attention upon the fact that the human being is basically an entity defined by relationships (node–existence), whose humanity is manifested through his/her responsibility towards people belonging to him/her and towards the human world (II.). This evinced image of the human being shows that he/she considers the existential needs and opportunities as representing the most basic elements of human life (basic structure of human life), whereas taking and giving are considered to be the elementary human manifestations. It states that the dynamic balance of giving and taking permits the unfolding of life and relationships, whilst the imbalance (a significant and lasting dominance of either giving, or of acceptance) causes stagnation and spiritual (as well as physical) illness. Contextual spiritual care can help regaining the long-lost balance, as it aims to dissolve the degrading and sickening relationship of subject–object (‘I–that’) by replacing it with the original relationship of subject–subject (‘I–you’), deriving from our created condition (III). The latter does allow particularly vulnerable (permanently disabled) people, who, due to their condition can give less, and are more dependent on others, to experience their own reliability and unique significance (IV.)